2013
DOI: 10.1002/macp.201300370
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Self‐Organization of PEG/α‐Cyclodextrin‐Based Polyrotaxanes in Solution: An Experimental and Theoretical Study

Abstract: Size exclusion chromatography coupled with light scattering (SEC/MALS), dynamic light scattering (DLS), steady‐state and time‐resolved fluorescence, as well as molecular dynamics (MD) simulations are used to study the behavior of several poly(ethylene glycol) (PEG)/α‐cyclodextrins (αCDs) polyrotaxanes (PRs) in solution. The number of CD units in any of the PRs studied is always smaller than that required to saturate the PEG chains. These PRs seem to aggregate in dimethyl sulfoxide (DMSO) solution. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 75 publications
1
5
1
Order By: Relevance
“…The stiffening of these molecules has recently been studied by Pinson et al using an exactly solvable theoretical model . On the other hand, experiments have shown that hairpin conformations are possible as well in free polyrotaxane molecules, if their rotor density remains significantly below the saturation density …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The stiffening of these molecules has recently been studied by Pinson et al using an exactly solvable theoretical model . On the other hand, experiments have shown that hairpin conformations are possible as well in free polyrotaxane molecules, if their rotor density remains significantly below the saturation density …”
Section: Introductionmentioning
confidence: 99%
“…While in the case of ordinary bottle brushes such a breakup would lead to the creation of only two fragments, a grafted polyrotaxane releases a large number of its rotors into the environment. Such a complex could therefore qualify as a drug-delivery system. , …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations